Proceedings of international conference on internet computing and information communications : ICICIC Global 2012 - Awasthi, Lalit Kumar; Masillamani, M. Roberts; Sridhar, S S.; Sathiakumar, Swamidoss (Advances in Intelligent Systems and Computing, 2014)
The book presents high quality research papers presented by experts in the International Conference on Internet Computing and Information Communications 2012, organized by ICICIC Global organizing committee (on behalf of The CARD Atlanta, Georgia, CREATE Conferences Inc). The objective of this book is to present the latest work done in the field of Internet computing by researchers and industrial professionals across the globe. A step to reduce the research divide between developed and under developed countries.